Unreadable Code in Novice Developers - Ávila, Daniel (2021)
Throughout his degree, a developer must face multiple challenges, one of the hardest is to understand unreadable code. This paper trying to identify the cause for the lack of usage of coding standards on students, throughout a survey carried out among first and second levels of degree of the Software Engineering. As well as acknowledging signs that would suggest an individual is prone to develop bad coding habits.